Applicability of existing models for the strength development of 3D-printed thixotropic concretes during hardening. Issue 3 (1st February 2023) - Castano-Alvarez, Ruben; Calderon-Uriszar-Aldaca, Iñigo; Marcos, Ignacio
Abstract: The special properties of 3 D-Printed Concrete in terms of rheology, deposition technology, and dosage substantially modify its mechanical properties after hardening. In this paper, comparisons are drawn between different concrete strength development models specified in the main Building-Codes and Standards and experimental data from tests on various thixotropic mortar mixes suitable for 3DPC. The aim was to develop an empirical procedure to improve the current models, so that their results could predict the properties of the 3DPC bulk materials more closely. An updated set of parameters for the models was obtained via curve-fitting of the models to the experimental data.